Simpler, Low-Cost Stealth - Zabri@Suhaimi, Siti Normi; Cahill, Robert; Schuchinsky, Alexander G. (Institution of Engineering and Technology, 2015)
FSS-based RAM that is thin, low-cost, robust and simple to manufacture can provide broadband absorption from a wide range of angles.